Consumption-based greenhouse gas emissions accounting with capital stock change highlights dynamics of fast-developing countries - Zhan-Ming Chen (Nature Portfolio, 2018)
Traditional carbon accounting attributes gap between consumption- and production-based emissions to international trade. The authors develop a dynamic model that incorporates capital stock change and find it improves estimates for fast-developing countries.